1961
DOI: 10.1677/joe.0.0230119
|View full text |Cite
|
Sign up to set email alerts
|

The Excretion of Individual 17-Oxosteroids in Cushing's Syndrome

Abstract: The urinary excretion levels of individual 17-oxosteroids in eight patients with Cushing's syndrome have been determined quantitatively. Using these values approximate secretion rates of cortisol and 11\g=b\-hydroxyandrostenedione were calculated and found to be elevated above the normal range. The excretion values for 11-deoxy-17-oxosteroids were highly variable, being below normal, normal or elevated in different patients. The excretion patterns in adrenocortical hyperplasia and carcinoma showed no character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1963
1963
1990
1990

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In hypothyroidism, anorexia nervosa, Cushing's syndrome, and other low T 3 syndromes, such as chronic illness, the deficiency of 5a-reductase activity appears to involve mainly hepatic 5«-reductase activity (21)(22)(23)(24)(25)(26). The defect is reversible, as demonstrated by MauvaisJarvis et al in studies of hypothyroid subjects (21).…”
Section: Discussionmentioning
confidence: 89%
“…In hypothyroidism, anorexia nervosa, Cushing's syndrome, and other low T 3 syndromes, such as chronic illness, the deficiency of 5a-reductase activity appears to involve mainly hepatic 5«-reductase activity (21)(22)(23)(24)(25)(26). The defect is reversible, as demonstrated by MauvaisJarvis et al in studies of hypothyroid subjects (21).…”
Section: Discussionmentioning
confidence: 89%
“…Androgen metabolism is altered (James, 1961), and it has been shown that the proportion of secreted cortisol con¬ verted to urinary 17-OHCS is decreased as the secretion rate increases (James & Caie, 1964). The continued administration of dexamethasone to normal subjects also causes increased formation of 5ß metabolites relative to 5a compounds (Wilson & Schenker, 1964).…”
Section: Discussionmentioning
confidence: 99%